Mechanisms for Expanding Harm Reduction for Opioid Use in Suburban and Rural U.S. Settings. (April 2023) - Montaque, Helena D. G.; Christenson, Erika; Spector, Antoinette; Wogen, Jenifer; McDonald, Madelyn; Weeks, Margaret R.; Li, Jianghong; Dickson-Gomez, Julia
The availability and adoption of Syringe Services Programs (SSPs) depends heavily on the towns and counties charged with implementing and sustaining these programs. Suburban and rural areas especially lack the community and political support for SSPs. We examined key informant in-depth interview data among professionals providing harm reduction services as well as some health department directors, doctors, and law enforcement officers from a three-state (Connecticut, Kentucky, and Wisconsin) study. Results revealed the challenges and emerging solutions for expanding harm reduction services in suburban and rural areas. Additional comparisons of experiences of those working in urban areas were highlighted. Overall, there were widespread similarities in challenges across the three states for providing harm reduction services in rural and suburban settings. Findings revealed potential directions to address the identified barriers and community-supported ideas to improve harm reduction efforts.